2013
DOI: 10.1002/ange.201209708
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Dynamic System of Three‐Dimensional Tetrahedral Polycatenanes

Abstract: Sechs auf einen Streich: Eine dynamische kombinatorische Bibliothek polycatenierter Tetraeder resultierte aus der Komplexbildung zwischen einem dynamischen tetraedrischen Fe4L6‐Käfig, aufgebaut aus Liganden mit elektronenarmem Naphthalindiimidkern, und einem elektronenreichen aromatischen Kronenether, 1,5‐Dinaphtho[38]krone‐10. Die Spezies höchster Ordnung in der Bibliothek ist das tetraedrische [7]Catenan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…SCCs typically display well-defined internal cavities with size and shape tunability, which provides the impetus for applications in host-guest chemistry [20][21][22] , catalysis 23 , molecular flasks 24 , supramolecular polymers [25][26][27] , bioengineering 28 and so on. Although quite a few metal complexes with attractive optical features are known 29,30 , light-emitting materials based on SCC platforms are relatively underdeveloped despite their prospects as advanced optical materials 31 .…”
mentioning
confidence: 99%
“…SCCs typically display well-defined internal cavities with size and shape tunability, which provides the impetus for applications in host-guest chemistry [20][21][22] , catalysis 23 , molecular flasks 24 , supramolecular polymers [25][26][27] , bioengineering 28 and so on. Although quite a few metal complexes with attractive optical features are known 29,30 , light-emitting materials based on SCC platforms are relatively underdeveloped despite their prospects as advanced optical materials 31 .…”
mentioning
confidence: 99%
“…248 (iii) Kuroda's macrotricyclic homo [2]catenane of quadruply interlocked cages, 249 (iv) a macrobicyclic [3]catenane, also known as a bis [2]catenane, 250 (v) a branched [6]catenane, 135 (vi) a side-chain poly [2]catenane, 251 (vii) a main-chain poly [2]catenane, which was originally introduced by Geerts,252 (viii) a macrotricyclic hetero [2]catenane, introduced by Becher 253 (ix) a macrobicyclic hetero [4]catenane resulting from a collaboration between Vögtle and Sauvage, 254 (x) covalently bridged [2]catenanes, which originated 106 as precatena nes in Schill's directed syntheses, but later became known [255][256][257] as pretzelanes or [2]pseudocatenanes (xi) a doubly threaded macrobicyclic [2]catenane introduced by Becher 258 under the title of a [3]pseudocatenane, a topology also known [259][260][261] as a 'handcuff' catenane, (xii) a [4]pseudocatenane introduced by Chen,262 (xiii) a macrotricyclic hetero [7]catenane arising from a Nitschke-Sanders collaboration, 263 (xiv) Vögtle's cyclic bis [2]catenane, 264 and (xv) Chiu's cyclic tetrakis [2]catenane. 265 The structures of many beautiful MIMs have also been elucidated in the solid state by X-ray crystallography.…”
Section: Topological Beautymentioning
confidence: 99%
“…[84] Additionally, parallel use of metal coordination chemistry, imine exchange reactions, and supramolecular interactions furnished fascinating results in the field of interlocked structures. Significant examples are the Borromean rings and Solomon knots reported by Stoddart et al [85] and the synthesis of tetrahedral polycatenanes reported by Sanders, Nitschke et al [86] Hydrazone Exchange Reaction Besides the imine exchange reaction, C=N exchange involving hydrazone formation has been also widely investigated in DCC, mainly because:…”
Section: Imine Exchange Reactionmentioning
confidence: 99%